The influence of perception of care and maternal protection on breastfeeding practices on the infants' third month of life - Salete de Matos; Juliana Rombaldi Bernardi; Luciano Santos Pinto Guimarães; Isabel Cristina Ribas Werlang; Clécio Homrich da Silva; Marcelo Zubaran Goldani (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to evaluate the influence of perception of care and maternal protection on breastfeeding practices on the infants' third month of life. Methods: longitudinal study with mother-infant pairs distributed in five groupsof gestational clinical conditions. The recruitment occurred in the period 2011 to 2016 at three hospitals in the public health systems in Porto Alegre, Brazil. The Parental Bonding Instrument and the Edinburgh Postpartum Depression Scale were assessed. Exclusive and prolonged breastfeeding were analyzed by questionnaires. Data were analyzed by one-way ANOVA with Tukey's post-hoc test, Kruskal-Wallis with Dunn's post-hoc test, or Pearson's chi-squared test. The significance was set at 5%. Results: 209 mother-infant pairs were investigated. Among those who did not practice breastfeeding, a lower perception of care, a higher perception of maternal protection, and a higher score of postpartum depression were observed (p=0.022, p=0.038, and p<0.001, respectively), when compared to peers who practiced. The control group had a significantly higher perception of care when compared to thediabetes mellitus group (p=0.006), and the perception of maternal protection and postpartum depression had no differences between the intrauterine groups (p>0.05). Conclusions: the perception of care and maternalprotection and the postpartum depressive symptomatology influenced breastfeeding at three months. It is possible to assume a transgenerational effect on breastfeeding, suggesting the existence of a complex model related to mental health in a sample of women who had different backgrounds of gestational clinical conditions